Kajian Literatur: Perbandingan Material Komposit Keramik C/C, C/SiC, dan Oxide/Oxide untuk Sistem Propulsi Rudal - Ridho Hotmartua Manurung; Sovian Aritonang (Rekayasa Material, Manufaktur dan Energi, 2026)
Ceramic Matrix Composites (CMCs)—comprising carbon–carbon (C/C), carbon–silicon carbide (C/SiC), and oxide–oxide variants—have emerged as pivotal materials in high-temperature missile propulsion systems due to their superior thermal and mechanical performance. Recent studies highlight the distinct characteristics of each material type. Specifically, C/C composites exhibit low density and high thermal conductivity, yet suffer from poor oxidation resistance. Conversely, C/SiC composites demonstrate excellent mechanical strength at elevated temperatures, while oxide–oxide composites offer robust oxidation stability but remain limited to intermediate operating temperatures. Despite these insights, an integrated comparative analysis focusing specifically on these three CMC types for propulsion applications has not yet been established. This study aims to address this research gap by conducting a systematic literature review across seven primary parameters: maximum operating temperature limit, oxidation resistance, mechanical strength, thermal shock resistance, strength-to-weight ratio, fracture toughness, and fatigue reliability. The analysis is synthesized from Scopus-indexed scientific literature and other credible databases to identify the most effective CMC system for developing lightweight, durable, and thermally stable missile propulsion components.